Lifetimes and emissions of SO2 from point sources estimated from OMI. Issue 6 (17th March 2015) - Fioletov, V. E.; McLinden, C. A.; Krotkov, N.; Li, C.
Abstract A new method to estimate sulfur dioxide (SO2) lifetimes and emissions from point sources using satellite measurements is described. The method is based on fitting satellite SO2 vertical column density to a three‐dimensional parameterization as a function of the coordinates and wind speed. An effective lifetime (or, more accurately, decay time) and emission rate are then determined from the parameters of the fit. The method was applied to measurements from the Ozone Monitoring Instrument (OMI) processed with the new principal component analysis (PCA) algorithm in the vicinity of approximately 50 large U.S. near‐point sources. The obtained results were then compared with available emission inventories. The correlation between estimated and reported emissions was about 0.91 with the estimated lifetimes between 4 and 12 h. It is demonstrated that individual sources with annual SO2 emissions as low as 30 kt yr−1 can produce a statistically significant signal in OMI data.